Comorbidities and complications of COVID-19 associated with disease severity, progression, and mortality in China with centralized isolation and hospitalization: A systematic review and meta-analysis - Chen, Zhe; Peng, Yingying; Wu, Xiaolei; Pang, Bo; Yang, Fengwen; Zheng, Wenke; Liu, Chunxiang; Zhang, Junhua (Frontiers in Public Health, 2022)
Background Coronavirus disease 2019 (COVID-19) cause life-threatening with high fatality rates and spread with high infectious worldwide. We aimed to systematically review the comorbidities and complications of COVID-19 that are associated with various disease severity, progression, and mortality in China, to provide contemporary and reliable estimates in settings with centralized isolation and hospitalization. Methods In this systematic review and meta-analysis, we searched four main English-language databases, and four main Chinese-language databases for observational studies published from inception to Jan 2022, to identify all related comorbidities and complications of COVID-19, in China region with centralized isolation and hospitalization, with disease severity, progression, and mortality. Literature search, data extraction, and quality assessment were independently conducted by two reviewers. We used generalized linear mixed model to estimate pooled effect sizes for any comorbidities and complications, and subgroup in gender ratio were done to further address the potential heterogeneity. RESULTS Overall, 187 studies describing 77013 patients including 54 different comorbidities and 46 various complications of COVID-19 were identified who met our inclusion criteria. The most prevalent comorbidities were hypertension (20.37% 95% confidence interval [CI;15.28-26.63], 19.29% [16.17-22.85], 34.72% [31.48-38.10], and 43.94% [38.94-49.06]) and diabetes (7.84% [5.78-10.54], 8.59% [7.25-10.16], 17.99% [16.29-19.84] and 22.68% [19.93-25.69]) in mild, moderate, severe, and critical cases. The most prevalent complications were liver dysfunction (10.00% [1.39-46.72]) in mild, acute liver injury (30.36% [27.70-33.16]; 43.69% [40.02-47.42]) in moderate and severe, acute respiratory distress syndrome (ARDS) (94.17% [20.78-99.90]) and respiratory failure (90.69% [28.08-99.59]) in critical. Renal insufficiency (odds ratio [OR] 17.43; [6.69-45.43]) in comorbidities and respiratory failure (OR 105.12 [49.48-223.33]) in complications were strongly associated in severe/critical than in mild/moderate cases. The highest estimated risk in intensive care unit (ICU) admission, progression, and mortality were autoimmune disease, nervous system disease, and stroke in comorbidities, shock and ARDS in complications. Conclusions Comorbidities and complications in inpatients with COVID-19 were positively associated with increased risk in severe and critical cases, ICU admission, exacerbation, and death during centralized isolation and hospitalization. Prompt identification of comorbidities and complications in inpatients with COVID-19 can enhance the prevention of disease progression and death and improve the precision of risk predictions.